Bressanone, via Castellano, settlement of the Final Bronze Age: remains of combustion structures? - Umberto Tecchiati; Giovanni Rizzi; Giovanni Tasca (IpoTESI di Preistoria, 2019)
Excavations carried out in 2002-2003 by the Office of Archaeological Heritage of Bolzano in Bressanone - Via Castellano, have allowed us to investigate a large settlement area (2000 m2) dating back to the Final Bronze Age. Among other features, three pits with heating traces on bottom and walls and a great amount of daub fragments in the filling have been found. Most of the daub fragments have flat or concave finished surfaces and on the opposite face the impressions of a support frame made up of small-diameter closely intertwined plant elements, with transversal elements of greater diameter (2-3 cm). It is possible that the daub fragments were relative to some kind of wattle and daub structures complementary to the firing pits.